2019
DOI: 10.1017/s1478951519001019
|View full text |Cite
|
Sign up to set email alerts
|

The utility of nursing instruments for daily screening for delirium: Delirium causes substantial functional impairment

Abstract: AbstractObjectiveNursing assessments have been recommended for the daily screening for delirium; however, the utility of individual items have not yet been tested. In a first step in establishing the potential of the electronic Patient Assessment-Acute Care (ePA-AC) as such, the impact of delirium on the functional domains was assessed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This study complements the previously reported usefulness of the functional domains of the ePA-AC (Bode et al, 2020) by the missing and equally useful domains related to cognition and consciousness, communication and interaction, sleep, respiration, pain, and wounds.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study complements the previously reported usefulness of the functional domains of the ePA-AC (Bode et al, 2020) by the missing and equally useful domains related to cognition and consciousness, communication and interaction, sleep, respiration, pain, and wounds.…”
Section: Discussionsupporting
confidence: 86%
“…The statistical procedures were previously described in a paper evaluating the functional domains of the ePA-AC (Bode et al, 2020) using the Statistical Package for Social Sciences (SPSS) version 25. Sociodemographic and clinical variables are described with means and standard deviations or medians and interquartile ranges, depending on parametric properties, as well as percentages for categorical variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) a nursing instrument most recently validated by our group for the diagnosis of delirium, the Ergebnisorientiertes PflegeAssessment Acute-Care (ePA-AC) ( 17 , 18 ) DSM-5-criteria ( 1 ), see also below.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum score is eight; scores of more than three indicate the presence of delirium. Each item is rated on the patient's behavior over the previous eight ( 15 , 18 ).…”
Section: Methodsmentioning
confidence: 99%